DAMPAK PANDEMI COVID-19 TERHADAP MENIKNYA PERNIKAHAN ANAK BAWAH UMUR DI KOTA PALOPO - Nirwana Halide (IAIN Palopo, 2021)
Child marriage is a serious issue that still occurs in various countries, including Indonesia. The COVID-19 pandemic has exacerbated the situation, with cases of child marriage increasing in various regions, including in the city of Palopo. This research aims to analyze the factors that influence the increase of child marriage cases during the COVID-19 pandemic in Palopo city, as well as provide solutions and recommendations to reduce and stop the practice. The research method used is qualitative with data collection techniques through interviews and observations. The results show that the factors that influence the increase of child marriage cases during the COVID-19 pandemic in Palopo city include economic factors, socio-cultural factors, and access to education and health. Solutions and recommendations include strengthening regulations, imposing strict sanctions, improving access to education and health for girls, as well as providing social support and protection for families experiencing economic difficulties. It is hoped that the results of this research can contribute to addressing the problem of child marriage during the COVID-19 pandemic in Palopo city and other areas.